Distribution and Genetic Diversity of Salmonella enterica in the Upper Suwannee River - Masoumeh Rajabi; Melissa Jones; Michael Hubbard; Gary Rodrick; Anita C. Wright (International Journal of Microbiology)
The Suwannee River spans the Florida/Georgia border to the Gulf of Mexico, and contributes to regional irrigation and recreational activities. Association of Salmonella enterica with these resources may result in the contamination of produce and disease outbreaks. Therefore, surface water was examined for the distribution of S. enterica at multiple time points from 4 sites on the upper Suwannee River. Isolates were confirmed by detection of the invA gene, and 96% of all samples were positive for the bacterium. Most probable number enumeration ranged from <18 to 5400 MPN/100 mL. Genetic diversity of these isolates (n=110) was compared to other environmental (n=47) or clinical (n=28) strains and to an online library (n=314) using DiversiLab rep-PCR. All strains showed >60% similarity and distributed into 16 rep-PCR genogroups. Most (74%) of the Suwannee River isolates were clustered into two genogroups that were comprised almost exclusively (97%) of just these isolates. Conversely, 85% of the clinical reference strains clustered into other genogroups. However, some Suwannee River isolates (12%) were clustered with these primarily clinically-associated genogroups, supporting the hypothesis that river water can serve as a disease reservoir and that pathogenic strains may persist or possibly originate from environmental sources.